Det farlige spørgsmål: Identitetsudfordringer for nye studerende ved en ung professionsuddannelse - Frandsen, Mads Kryger; Kokholm, Trine; Aagaard, Kaare (Tidsskrift for Professionsstudier, 2023)
This article explores understandings of professional identity among newly started students at the Public Administration Bachelor-education at a Danish University College and analyzes tensions linked to these. Based on data from focus group interviews and ‘study start tests’ the article focuses on perceived advantages and disadvantages of initiating an education with short history, low public visibility, but also great flexibility in relation to potential career paths. Based on Kåre Heggen's theoretical work, the analysis highlights the distinction between an internal and an external view of the education as crucial for understanding the students’ statements. A key observation is that the students generally consider flexibility in relation to future career paths to be a strength, but at the same time miss the external recognition associated with more established professions. The article thereby shows how many new students, on the one hand, request the legitimacy linked to clear professional images, but on the other hand, highlight their appreciation of the flexibility and open-ended nature of this particular education. It thus points to a central, but also difficult, challenge with relevance across a wide range of University College educations: How to balance a strong collective identity with the needs of individualization and flexibility?